Sodium-ion battery composite positive electrode material and preparation method thereof

By first synthesizing layered transition metal oxides in the sodium ion battery positive electrode material and mixing them with polyanionic material, spray drying technology is used to solve the problem of low compaction density and energy density of the polyanionic sodium ion battery positive electrode material, and preparing High-performance sodium ion battery composite positive electrode material.

CN119284981APending Publication Date: 2025-01-10JIANGSU YANGGUANG TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411294296.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The positive electrode material of polyanionic sodium ion battery has problems with low compaction density and low energy density.

Method used

The layered transition metal oxide positive electrode material is first synthesized and mixed with the polyanionic raw material in the early stage. The uniform dispersion is achieved through spray drying technology, and the uniform distribution is maintained during the subsequent sintering process to prevent phase separation and degenerate accumulation, and high preparation is achieved. Compound positive electrode material of compaction density and high energy density.

Benefits of technology

The composition uniformity of the composite positive electrode material is achieved, the compaction density, high capacity and high energy density of sodium ion batteries are improved, and the performance is more stable when used.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the field of secondary batteries, in particular to a sodium ion battery composite positive electrode material and a preparation method thereof. The preparation method comprises the following steps: preparing a layered transition metal oxide positive electrode material, mixing the layered transition metal oxide positive electrode material with a polyanion raw material, spray-drying, sintering and the like. Compared with the prior art, the preparation method has the advantages that the layered transition metal oxide positive electrode material is synthesized firstly, the layered transition metal oxide positive electrode material and the polyanion raw material are mixed in the early stage, and the spray drying technology is adopted, so that the two materials can be uniformly dispersed on the microscopic level; the uniform distribution is maintained in the subsequent sintering process, the phase splitting and segregation phenomena of the material are prevented, the component uniformity of the composite positive electrode material is ensured, and the prepared sodium ion battery has higher compaction density, high capacity, high energy density and more stable performance during use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of secondary batteries, and in particular to a composite positive electrode material for a sodium ion battery and a preparation method thereof. Background Art

[0002] Secondary battery technology, especially sodium-ion batteries, has abundant reserves of sodium on earth, a wide range of sources, and a price far lower than lithium. Therefore, sodium-ion batteries have attractive application prospects in the field of grid energy storage; compared with the fluctuating costs of lithium-ion batteries, sodium-ion batteries use abundant sodium resources with low costs, and sodium-ion batteries have similar structures and working principles to lithium-ion batteries, so the market demand for sodium-ion batteries is constantly expanding, and the positive electrode material is the most critical component of sodium-ion batteries.

[0003] At present, among the reported sodium-ion battery positive electrode materials, polyanion sodium-ion battery positive electrode materials are considered to be very promising positive electrode materials due to their advantages such as high working potential, low cost and high safety; however, polyanion sodium-ion battery positive electrode materials also have clear disadvantages, such as their low compaction density and low energy density.

[0004] In view of the above-mentioned defects of the current polyanion sodium ion battery positive electrode materials, it is indeed necessary to provide a technical solution to the above-mentioned problems. Summary of the invention

[0005] The object of the present invention is to provide a composite positive electrode material for a sodium ion battery, which has a high compaction density and a high energy density, and has a simple preparation process, low cost and is easy to produce.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a composite positive electrode material for a sodium ion battery comprises the following steps:

[0008] Step 1: Pumping a mixed solution of manganese salt, nickel salt and iron salt, a precipitant and a complexing agent into a reaction kettle at the same time and stirring to obtain a spherical precursor powder;

[0009] Step 2: weighing the spherical precursor powder, the first sodium source and the dopant, uniformly mixing them, and sintering them at 700-1000° C. for 5-30 hours in an air atmosphere to obtain a layered transition metal oxide positive electrode material;

[0010] Step 3: adding the layered transition metal oxide positive electrode material and the polyanion raw material into a sand mill, wet sand milling, and then spray drying using a spray dryer;

[0011] Step 4: Sinter the spray-dried powder to obtain a composite positive electrode material for a sodium ion battery.

[0012] Preferably, the chemical formula of the layered transition metal oxide positive electrode material is: NaNi 0.33 Fe 0.33 Mn 0.33 O2.

[0013] Preferably, the chemical formula of the sodium ion battery composite positive electrode material is NaNi 0.33 Fe 0.33 Mn 0.33 O2 / Na 2+ 2x Fe 2-x (SO4)3@C, where x satisfies the relationship: 0.2≤x≤0.25.

[0014] Preferably, in step one, the manganese salt includes at least one of manganese sulfate, manganese chloride, manganese nitrate, manganese acetate and manganese citrate; the nickel salt includes at least one of nickel sulfate, nickel chloride, nickel nitrate, nickel acetate and nickel citrate; the iron salt includes at least one of ferrous sulfate, ferrous chloride, ferrous nitrate, ferrous acetate and ferrous citrate; the precipitant solution includes at least one of hydroxide precipitation solution, carbonate solution and oxalate solution; the complexing agent solution includes at least one of ammonia water and disodium EDTA.

[0015] Preferably, in step 1, the molar ratio of manganese, nickel and iron in the mixed solution is 1:1:1; and the concentration of the mixed solution is 1 mol / L to 3 mol / L.

[0016] Preferably, in the step 2, the mass ratio of the spherical precursor to the first sodium source is 1:(1-1.05).

[0017] Preferably, in the step three, the polyanion raw material includes an iron source, a sulfur source, a carbon source and a second sodium source, and the molar ratio of iron, sulfur, carbon and sodium in the iron source, the sulfur source, the carbon source and the second sodium source is (1.75-1.8):3:(0.1-0.15):(2.4-2.5); the mass ratio of the layered transition metal oxide positive electrode material and the polyanion raw material is (10-20):(80-90).

[0018] Preferably, in step three, the frequency of the spray drying atomizer is 150-400 Hz; the inlet air temperature is 150-250°C.

[0019] Preferably, in the step 4, the sintering temperature is 200-400° C., and the sintering atmosphere is nitrogen or argon.

[0020] The present invention also provides a composite positive electrode material, which is prepared by the above-mentioned method for preparing the composite positive electrode material for a sodium ion battery.

[0021] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention provides a method for preparing a composite positive electrode material for a sodium ion battery, and the present invention can achieve uniform dispersion of the two materials at a microscopic level by first synthesizing a layered transition metal oxide positive electrode material, and mixing the layered transition metal oxide positive electrode material with a polyanion raw material in an early stage, and adopting a spray drying technology; this uniform distribution is maintained during the subsequent sintering process, thereby preventing phase separation and segregation of the material, ensuring the uniformity of the composition of the composite positive electrode material, and the prepared sodium ion battery has a higher compaction density, high capacity and high energy density, and has more stable performance during use. DETAILED DESCRIPTION

[0022] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] According to a first aspect of the present invention, the present invention provides a method for preparing a composite positive electrode material for a sodium ion battery, comprising the following steps:

[0024] Step 1: Pumping a mixed solution of manganese salt, nickel salt and iron salt, a precipitant and a complexing agent into a reaction kettle at the same time and stirring to obtain a spherical precursor powder;

[0025] Step 2: weighing the spherical precursor powder, the first sodium source and the dopant, uniformly mixing them, and sintering them at 700-1000° C. for 5-30 hours in an air atmosphere to obtain a layered transition metal oxide positive electrode material;

[0026] Step 3: adding the layered transition metal oxide cathode material and the polyanion raw material into a sand mill, wet sand milling, and then spray drying using a spray dryer;

[0027] Step 4: Sinter the spray-dried powder to obtain a composite positive electrode material for a sodium ion battery.

[0028] Among them, the present invention first synthesizes a layered transition metal oxide positive electrode material, mixes the layered transition metal oxide positive electrode material with a polyanion raw material in an early stage, and adopts a spray drying technology, so as to achieve uniform dispersion of the two materials at a microscopic level; this uniform distribution is maintained during the subsequent sintering process, preventing the phase separation and segregation of the material, ensuring the uniformity of the composition of the composite positive electrode material, and the prepared sodium ion battery has a higher compaction density, high capacity and high energy density, and the performance is more stable during use.

[0029] The layered transition metal oxide positive electrode material prepared by the present invention can be directly purchased or prepared by oneself.

[0030] In one embodiment of the present invention, the chemical formula of the layered transition metal oxide positive electrode material is: NaNi 0.33 Fe 0.33 Mn 0.33 O2.

[0031] In one embodiment of the present invention, the chemical formula of the sodium ion battery composite positive electrode material is NaNi 0.33 Fe 0.33 Mn 0.33 O2 / Na 2+2x Fe 2-x (SO4)3@C, where x satisfies the relationship: 0.2≤x≤0.25.

[0032] In one embodiment according to the present invention, in step one, the manganese salt includes at least one of manganese sulfate, manganese chloride, manganese nitrate, manganese acetate and manganese citrate; the nickel salt includes at least one of nickel sulfate, nickel chloride, nickel nitrate, nickel acetate and nickel citrate; the iron salt includes at least one of ferrous sulfate, ferrous chloride, ferrous nitrate, ferrous acetate and ferrous citrate; the precipitant solution includes at least one of hydroxide solution, carbonate solution and oxalate solution; and the complexing agent solution includes at least one of ammonia water and disodium EDTA.

[0033] In one embodiment of the present invention, in step 1, the molar ratio of manganese, nickel and iron in the mixed solution is 1:1:1; the concentration of the mixed solution is 1 mol / L to 3 mol / L. Limiting the molar ratio of manganese, nickel and iron and the concentration range of the mixed solution can prepare a layered transition metal oxide positive electrode material with better performance, which can be doped into a polyanion type sodium ion battery positive electrode material to better improve the compaction density and energy density of the polyanion type sodium ion battery positive electrode material.

[0034] In one embodiment according to the present invention, in step 2, the mass ratio of the spherical precursor to the first sodium source is 1:(1-1.05).

[0035] In one embodiment of the present invention, in step 2, the dopant is at least one of zinc oxide, magnesium oxide, and zirconium oxide; and the amount of the dopant is 0.01 to 5 mol%.

[0036] In one embodiment according to the present invention, in step three, the polyanion raw material includes an iron source, a sulfur source, a carbon source and a second sodium source, and the molar ratio of the iron element, the sulfur element, the carbon element and the sodium element in the iron source, the sulfur source, the carbon source and the second sodium source is (1.75-1.8):3:(0.1-0.15):(2.4-2.5); the mass ratio of the layered transition metal oxide positive electrode material and the polyanion raw material is (10-20):(80-90); for example, it can be 10:90, 11:89, 12:88, 13:87, 14:86, 15:85, 16:84, 17:83, 18:82, 19:81, 20:80; here, limiting the mass ratio range of the layered transition metal oxide positive electrode material and the polyanion raw material can better utilize the high capacity and high compaction density of the layered transition metal oxide positive electrode material to improve the compaction density and energy density of the polyanion sodium ion battery positive electrode material. The compaction of layered transition metal oxide cathode materials is higher than that of polyanion cathode materials. After the addition of layered transition metal oxide cathode materials, the structure of polyanion cathode materials becomes denser, and the compaction density will increase accordingly; the gram capacity of layered transition metal oxide cathode materials is higher than that of polyanion cathode materials. After the addition of layered transition metal oxide cathode materials, the sodium ions inserted and deintercalated during charge and discharge of composite cathode materials increase, and the gram capacity will increase accordingly; similarly, after the compaction density and gram capacity of composite cathode materials increase, the energy density will increase accordingly. When the proportion of layered transition metal oxide cathode materials is too large, the stability of the material structure deteriorates; when the proportion of layered transition metal oxide cathode materials is too small, the gram capacity and compaction of the material cannot be significantly improved.

[0037] In one embodiment of the present invention, in step three, the frequency of the atomizer for spray drying is 150-400 Hz; the inlet air temperature is 150-250°C.

[0038] In one embodiment of the present invention, in step 4, sintering is performed by step sintering, including primary sintering, secondary sintering and tertiary sintering in sequence, wherein the temperature of the primary sintering is 200-250°C, the time is 10-15h, the temperature of the secondary sintering is 250-300°C, the time is 5-10h, and the tertiary sintering is 300-400°C, the time is 1-5h. The present invention adopts multiple sintering for the composite positive electrode material of the sodium ion battery, which can further promote the growth of the positive electrode material grains and the improvement of the solidity, make the crystal structure more compact, and thus enhance the electrochemical performance of the material. After the primary sintering, the positive electrode material may have the problem of incomplete stability of the lattice structure, more impurities and defects, therefore, the present invention further adopts secondary sintering and tertiary sintering to recrystallize the material at a higher temperature, the lattice is more stable, thereby eliminating these impurities and defects, and improving the purity and performance of the material. Multiple sintering can also improve the particle size and distribution of the positive electrode material, making it more uniform, which is conducive to improving the charge / discharge rate and cycle life of the battery.

[0039] In one embodiment of the present invention, in step 4, the sintering atmosphere is nitrogen or argon.

[0040] According to the second aspect of the present invention, the present invention also provides a sodium ion battery composite positive electrode material, which is prepared by the above-mentioned method for preparing the sodium ion battery composite positive electrode material.

[0041] The present invention will be further described below by means of specific examples.

[0042] Example 1

[0043] Preparation of positive electrode materials:

[0044] Step 1: Pumping a mixed solution of manganese sulfate, nickel sulfate, and ferrous sulfate (wherein the molar ratio of Mn:Ni:Fe is 1:1:1) and a precipitant sodium hydroxide and a complexing agent ammonia solution into a reaction kettle by a peristaltic pump and stirring to obtain a spherical precursor powder; wherein the concentration of the mixed solution is 2 mol / L;

[0045] Step 2: Precursor and sodium source: Weigh spherical precursor powder, sodium source and dopant zinc oxide in a molar ratio of 1:1 and mix them evenly, and sinter them at 950° C. for 20 hours in an air atmosphere to obtain a layered transition metal oxide positive electrode material; wherein the amount of the dopant is 0.5 mol%;

[0046] Step 3: Add layered transition metal oxide positive electrode material, iron source, sulfur source, carbon source, sodium source (wherein the molar ratio of Fe:S:C:Na is 1.8:3:0.1:2.4) into a sand mill, and perform wet sand milling; wherein the layered transition metal oxide positive electrode material accounts for 10%; the sand milled material is spray dried using a spray dryer; wherein the spray drying atomizer frequency is 300 Hz; and the air inlet temperature is 250°C;

[0047] Step 4: Sinter the spray-dried powder in a nitrogen atmosphere at 380° C. for 20 h to obtain a composite positive electrode material for a sodium ion battery.

[0048] Preparation of positive electrode:

[0049] The mixture was homogenized in a weight ratio of active material: conductive agent: binder = 95:2.5:2.5, and after being stirred evenly, a positive electrode slurry was obtained. The slurry was coated on Al foil, baked, rolled, and cut into strips to obtain a positive electrode sheet.

[0050] Preparation of negative electrode:

[0051] Hard carbon, conductive agent carbon nanotubes, binder styrene butadiene rubber, and thickener sodium carboxymethyl cellulose are stirred and mixed in deionized water at a mass ratio of 97.2:1.2:0.8:0.8. After being mixed evenly, the negative electrode slurry is coated on Cu foil, baked, rolled, and cut into strips to obtain a negative electrode sheet.

[0052] Preparation of diaphragm:

[0053] Polyethylene (PE) polymer film is used as the isolation membrane.

[0054] Preparation of electrolyte

[0055] An organic solution is obtained by uniformly mixing the following components and mass ratios: ethylene carbonate (EC): propyl propionate (PP): vinylene carbonate (VC): diethyl carbonate (DEC): propylene carbonate (PC) = 22:25:3:28:22; sodium hexafluorophosphate is added to the organic solution, and the mass ratio of the added mass to the organic solution is 9.5:90.5; and an electrolyte is obtained after uniform mixing.

[0056] Preparation of sodium ion batteries

[0057] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order and wound to obtain an electrode assembly; the electrode assembly is placed in a packaging shell, an electrolyte is injected into the packaging shell and the packaging is packaged to finally obtain a sodium ion battery.

[0058] Example 2

[0059] Different from Example 1, the sintering in step 4 is a step-by-step sintering, with the first sintering temperature being 200° C. for 10 h, the second sintering temperature being 300° C. for 7 h, and the third sintering temperature being 400° C. for 3 h.

[0060] The rest is the same as Example 1 and will not be described again here.

[0061] Example 3

[0062] Different from Example 1, the layered transition metal oxide positive electrode material in this example accounts for 13%;

[0063] The rest is the same as Example 1 and will not be described again here.

[0064] Example 4

[0065] Different from Example 1, the layered transition metal oxide positive electrode material in this example accounts for 15%;

[0066] The rest is the same as Example 1 and will not be described again here.

[0067] Example 5

[0068] Different from Example 1, the layered transition metal oxide positive electrode material in this example accounts for 18%;

[0069] The rest is the same as Example 1 and will not be described again here.

[0070] Example 6

[0071] Different from Example 1, the layered transition metal oxide positive electrode material in this example accounts for 20%;

[0072] The rest is the same as Example 1 and will not be described again here.

[0073] Comparative Example 1

[0074] Different from Example 1, the positive electrode material of this comparative example is a polyanion type sodium ion battery positive electrode material; the specific preparation method is as follows:

[0075] 1) adding an iron source, a sulfur source, a carbon source, and a sodium source (wherein the molar ratio of Fe:S:C:Na is 1.8:3:0.1:2.4) into a sand mill, and wet sand milling is performed; the sand milled material is spray dried using a spray dryer; wherein the spray drying atomizer frequency is 300 Hz; and the air inlet temperature is 250° C.;

[0076] 2) The spray-dried powder is then sintered in a nitrogen atmosphere at 380° C. for 20 h to obtain a polyanionic positive electrode material.

[0077] The rest is the same as Example 1 and will not be described again here.

[0078] Comparative Example 2

[0079] Different from Example 1, the layered transition metal oxide positive electrode material in this comparative example accounts for 9%;

[0080] The rest is the same as Example 1 and will not be described again here.

[0081] Comparative Example 3

[0082] Different from Example 1, the layered transition metal oxide positive electrode material in this comparative example accounts for 25%;

[0083] The rest is the same as Example 1 and will not be described again here.

[0084] Comparative Example 4

[0085] The difference from Example 1 is that: in step 3, no layered metal oxide sodium ion battery positive electrode material is added, a polyanion type sodium ion battery positive electrode material is first prepared, and then the layered metal oxide sodium ion battery positive electrode material and the polyanion type sodium ion battery positive electrode material are mixed; wherein the specific preparation method of the composite positive electrode material is as follows:

[0086] Step 1: Pumping a mixed solution of manganese sulfate, nickel sulfate, and ferrous sulfate (wherein the molar ratio of Mn:Ni:Fe is 1:1:1) and a precipitant sodium hydroxide and a complexing agent ammonia solution into a reaction kettle by a peristaltic pump and stirring to obtain a spherical precursor powder; wherein the concentration of the mixed solution is 2 mol / L;

[0087] Step 2: Precursor and sodium source: Weigh the spherical precursor powder, sodium source and dopant in a molar ratio of 1:1, mix them evenly, and sinter them at 950° C. for 20 h in an air atmosphere to obtain a layered transition metal oxide positive electrode material; wherein the amount of the dopant is 5 mol%).

[0088] Step 3: adding an iron source, a sulfur source, a carbon source, and a sodium source (wherein the molar ratio of Fe:S:C:Na is 1.8:3:0.1:2.4) into a sand mill, and wet sand milling; spray drying the sand milled material using a spray dryer; wherein the spray drying atomizer frequency is 300 Hz; and the air inlet temperature is 250°C;

[0089] Step 4: sintering the spray-dried powder in a nitrogen atmosphere to obtain a polyanion sodium ion battery positive electrode material;

[0090] Step 5: Mix the layered transition metal oxide positive electrode material obtained in step 2 with the polyanion sodium ion battery positive electrode material obtained in step 4, wherein the layered transition metal oxide positive electrode material accounts for 10%; sinter to obtain a composite material.

[0091] The rest is the same as Example 1 and will not be described again here.

[0092] The positive electrode materials of Examples 1 to 6 and Comparative Examples 1 to 4 were subjected to a compaction density test, and the sodium ion batteries of Examples 1 to 6 and Comparative Examples 1 to 4 were subjected to an electrical performance test. The test results are shown in the following table.

[0093] Table 1

[0094]

[0095]

[0096] It can be seen from Table 1 that the experimental data of Examples 1 to 6 and Comparative Examples 2 to 3 show that the experimental data of Examples 1 to 6 are better than the experimental data of Comparative Examples 2 to 3, indicating that limiting the mass ratio range of the layered transition metal oxide positive electrode material and the polyanion raw material can better utilize the high capacity and high compaction density of the layered transition metal oxide positive electrode material to improve the compaction density and energy density of the polyanion sodium ion battery positive electrode material.

[0097] It can be seen from the data of Examples 1, 3, 4, 5 and 6 that the various performances of Example 4 are better than those of other examples, indicating that when the mass proportion of the layered transition metal oxide positive electrode material is 15%, the various performances of the sodium ion battery composite positive electrode material are best improved.

[0098] It can be seen from the data of Example 1 and Comparative Example 1 that all the data of Example 1 are better than those of Comparative Example 1, indicating that the present invention prepares a composite positive electrode material for a sodium ion battery with high compaction density, high capacity and high energy density by first synthesizing a layered transition metal oxide positive electrode material and directly mixing the layered transition metal oxide positive electrode material in the preparation of a composite positive electrode material for a sodium ion battery. The two positive electrode materials in the positive electrode material are more evenly distributed, and the performance of the prepared sodium ion battery is more stable when used.

[0099] It can be seen from the experimental data of Example 1 and Comparative Example 4 that the experimental data of Example 1 is better than the data of Comparative Example 4, indicating that the present invention directly mixes the layered transition metal oxide positive electrode material in the preparation of the sodium ion battery composite positive electrode material to prepare a sodium ion battery composite positive electrode material with high compaction density, high capacity and high energy density.

[0100] It can be seen from the data of Example 1 and Example 2 that the experimental data of Example 2 is better than the data of Example 1, which shows that the present invention adopts a multiple sintering method, which can further promote the growth of the positive electrode material grains and improve the firmness, making the crystal structure denser, thereby enhancing the electrochemical properties of the material; it can recrystallize the material at a higher temperature, and the lattice is more stable, thereby eliminating these impurities and defects and improving the purity and performance of the material; it can also improve the particle size and distribution of the positive electrode material to make it more uniform, which is beneficial to improving the charge / discharge rate and cycle life of the battery.

[0101] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A method for preparing a composite positive electrode material for a sodium ion battery, characterized in that The following steps are involved: Step 1: Pumping a mixed solution of manganese salt, nickel salt and iron salt, a precipitant and a complexing agent into a reaction kettle at the same time and stirring to obtain a spherical precursor powder; Step 2: weighing the spherical precursor powder, the first sodium source and the dopant, uniformly mixing them, and sintering them at 700-1000° C. for 5-30 hours in an air atmosphere to obtain a layered transition metal oxide positive electrode material; Step 3: adding the layered transition metal oxide positive electrode material and the polyanion raw material into a sand mill, wet sand milling, and then spray drying using a spray dryer; Step 4: Sinter the spray-dried powder to obtain a composite positive electrode material for a sodium ion battery.

2. The method for preparing a composite positive electrode material for a sodium ion battery according to claim 1, characterized in that: In step 2, the chemical formula of the layered transition metal oxide positive electrode material is: NaNi 0.33 Fe 0.33 Mn 0.33 O2.

3. The method for preparing a composite positive electrode material for a sodium ion battery according to claim 1, characterized in that: In step 4, the chemical formula of the sodium ion battery composite positive electrode material is NaNi 0.33 Fe 0.33 Mn 0.33 O2 / Na 2+2x Fe 2-x (SO4)3@C, where x satisfies the relationship: 0.2≤x≤0.

25.

4. The method for preparing a composite positive electrode material for a sodium ion battery according to claim 1, characterized in that: In the step 1, the manganese salt includes at least one of manganese sulfate, manganese chloride, manganese nitrate, manganese acetate and manganese citrate; the nickel salt includes at least one of nickel sulfate, nickel chloride, nickel nitrate, nickel acetate and nickel citrate; the iron salt includes at least one of ferrous sulfate, ferrous chloride, ferrous nitrate, ferrous acetate and ferrous citrate; the precipitant solution includes at least one of hydroxide solution, carbonate solution and oxalate solution; the complexing agent solution includes at least one of ammonia water and disodium EDTA.

5. The method for preparing a composite positive electrode material for a sodium ion battery according to claim 1, characterized in that: In the step 1, the molar ratio of manganese element, nickel element and iron element in the mixed solution is 1:1:1; the concentration of the mixed solution is 1 mol / L to 3 mol / L.

6. The method for preparing a composite positive electrode material for a sodium ion battery according to claim 1, characterized in that: In the step 2, the mass ratio of the spherical precursor to the first sodium source is 1:(1-1.05).

7. The method for preparing a composite positive electrode material for a sodium ion battery according to claim 1, characterized in that: In the step three, the polyanion raw material includes an iron source, a sulfur source, a carbon source and a second sodium source, and the molar ratio of iron, sulfur, carbon and sodium in the iron source, the sulfur source, the carbon source and the second sodium source is (1.75-1.8):3:(0.1-0.15):(2.4-2.5); the mass ratio of the layered transition metal oxide positive electrode material and the polyanion raw material is (10-20):(80-90).

8. The method for preparing a composite positive electrode material for a sodium ion battery according to claim 1, characterized in that: In the step 3, the frequency of the spray drying atomizer is 150-400 Hz; the inlet air temperature is 150-250°C.

9. The method for preparing a composite positive electrode material for a sodium ion battery according to claim 1, characterized in that: In the step 4, the sintering temperature is 200-400° C., and the sintering atmosphere is nitrogen or argon.

10. A composite positive electrode material for a sodium ion battery, characterized in that: The composite positive electrode material for sodium ion batteries is prepared by the preparation method of the composite positive electrode material for sodium ion batteries according to any one of claims 1 to 9.

Citation Information

Cited By

  • Low-cost high-voltage-resistant composite positive electrode material and preparation method thereof

    CN120072894A